2014
DOI: 10.1016/j.contraception.2014.05.085
|View full text |Cite
|
Sign up to set email alerts
|

Provider barriers to family planning access in urban Kenya

Abstract: Objective-A better understanding of the prevalence of service provider-imposed barriers to family planning can inform programs intended to increase contraceptive use. This study, based on data from urban Kenya, describes the frequency of provider self-reported restrictions related to clients' age, parity, marital status, and third party consent, and considers the impact of facility type and training on restrictive practices.Study Design-Trained data collectors interviewed 676 service providers at 273 health ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 8 publications
2
31
1
Order By: Relevance
“…Comparable findings about discrimination in type of provision based on parity have been noted in other studies in Kenya, South Africa, and Uganda (Wood and Jewkes ; Nalwadda et al. ; Tumlinson, Okigbo, and Speizer ).…”
Section: Young Adult Women's Use Of Modern Contraceptive Methods In Ssupporting
confidence: 49%
See 1 more Smart Citation
“…Comparable findings about discrimination in type of provision based on parity have been noted in other studies in Kenya, South Africa, and Uganda (Wood and Jewkes ; Nalwadda et al. ; Tumlinson, Okigbo, and Speizer ).…”
Section: Young Adult Women's Use Of Modern Contraceptive Methods In Ssupporting
confidence: 49%
“…For example, a survey of 20 public and private family planning service providers throughout all four districts of Uganda found that one-quarter of providers reported women needed to be a minimum age or have a minimum number of children to be referred for long-acting contraception methods (Wright et al 2017). Comparable findings about discrimination in type of provision based on parity have been noted in other studies in Kenya, South Africa, and Uganda (Wood and Jewkes 2006;Nalwadda et al 2011;Tumlinson, Okigbo, and Speizer 2014).…”
Section: Why Might Contraceptive Use Depend On Parity Status?contrasting
confidence: 39%
“…From the studies published between 2000 and 2019, a total of 11 272 participants were included in this review with the sample size ranging from 31 to 2 377. and perceptions of HCW's by ten studies (34,(37)(38)(39)(40)46,51,53,54,56,57). A detailed summary of the study characteristics is outlined in Table 2 and Table 3 presents the characteristics of the HCWs included in each study.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Using the quality assessment tool designed specifically for KAP studies, a total score out of was assigned to each study (27). Eight studies (32)(33)(34)42,45,47,49,53) scored at least 15 or higher indicating good quality and eleven (35)(36)(37)41,43,44,46,48,(50)(51)(52) scored 14 or less indicating low quality. The three studies (38)(39)(40) that utilised a mixed-method study design were indicative of good quality.…”
Section: Quality Of Studiesmentioning
confidence: 99%
“…In many countries where pre-exposure prophylaxis (PrEP) is available, AGYW are prioritized for PrEP outreach (2), yet early evidence demonstrates suboptimal PrEP uptake and coverage among AGYW (3,4). The gap in implementation may be partially explained by the unique barriers AGYW face when accessing sexual and reproductive health (SRH) services in healthcare facilities, such as stigma and provider bias (5)(6)(7)(8)(9). Shortages of workers and supplies also impede delivery of services at many facilities (10), forcing AGYW to travel longer distances at greater costs (11,12).…”
Section: Introductionmentioning
confidence: 99%